Analysis of the Effectiveness in Planning and Realization Regional Income and Expenditure Budget By the Government of Palangka Raya City Year 2019-2020 - Nusan, Yahya; Benius, Benius; Hukom, Alexandra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study was aimed to determine the effectiveness of budget planning and the efficiency of realization of regional income and expenditure budgets by the Government of Palangka Raya city. The type of research was descriptive method by using quantitative approach. The data taken was a summary of the Budget Work Plan and Budget Realization from 2019 to 2020 which was obtained from the Government of Palangka Raya city Financial System, SIMDA. The data processing technique used was the calculation of the effectiveness ratio and the efficiency ratio of budget realization. Based on the results of calculations and data collection on planning and budget realization, it could be stated that the Government of Palangka Raya city had succeeded in compiling and planning its budget well up to the realization stage. However, it could also be seen that the realization of the budget was less efficient because the expenditure was greater than the income.